MODERN THEORY OF ETIOPATHOGENESIS AND PREVENTION OF PREECLAMPSIA - M.F. DODKHOEVA; F.Z. OLIMOVA (Avicenna Tajik State Medical University, 2017)
Based on the analysis of world literature, found that preeclampsia, as the leading cause of maternal and perinatal morbidity and mortality, is currently one of the unresolved obstetric questions in the world. The negative impact of preeclampsia on pregnancy and perinatal outcomes affect the quality of life not only of the mother but also of the future descendants, which is a public health problem and which must be addressed especially to developing countries.